THU0226 Clinical features and mortality causes in a large cohort of spanish patients with anca associated vasculitides. (23rd January 2014) - Solans-Laqué, R.; Caminal, L.; Saez, L.; Rios, J.J.; Zamora, M.; Solanich, X.; Rodriguez, M.; Lopez-Dupla, M.; Castillo, M.J.; Fonseca, E.; Calleja, J.L.; Fanlo, P.; et al.
Abstract : Background: Antineutrophil cytoplasmic autoantibody (ANCA) associated vasculitides (AAV) are uncommon chronic and relapsing diseases characterized by inflammatory cell infiltration and necrosis of blood vessel walls. They often have overlapping clinical and pathological manifestations that make difficult to reach a precise diagnosis. AAV are still related to a high mortality and morbidity in spite of current therapies. Objectives: To describe the clinical features present at diagnosis and to investigate the causes of mortality in a large cohort of patients with AAV from Spain. Methods: We analyzed the demographic, clinical and laboratory features of all patients diagnosed with AAV in 13 different Hospitals from Spain, between January 1995 and December 2010. The statistical analysis was performed using the SPSS v15.0. Results: Two hundred and forty-six patients were included: 109 WG, 97 MPA and 40 CSS. ANCA were positive in 87% of cases: 35.4% C-ANCA and 51.6% P-ANCA. The mean age at diagnosis was 55.3±17.4 years. The mean time to diagnosis was 2±13.7 months. The most frequent symptoms at diagnosis were fever (50.4%), constitutional symptoms (49%), arthralgia (55%), hypertension (30%), hemoptisis (21.5%) and purpura (21%). Renal failure was present in 48.8% of patients, pulmonary involvement in 45.5%, pulmonary-renal syndrome in 11%, and cardiac involvement in 9%. Sensory peripheral neuropathy was detected in 26% of cases and cerebrovascular accidents (CVA) in 4.5%. Ear, nose and throat (ENT) was observed in 35% of cases and eye involvement in 15%. Renal involvement was significantly higher in patients with P-ANCA and ENT involvement in patients with C-ANCA. Necrotizing glomerulonephritis on biopsy was evidenced in 30% of cases. All patients received oral glucocorticoid treatment. Cyclophosphamide was given to 209 patients (39% intravenous and 46% oral). Dialysis was required in 18% of cases and plasma exchange in 6.5%. During the follow-up 34.6% of patients suffered bacterial infections, 12% sepsis, 14% opportunistic infections, and 4.9% developed neoplasm. Opportunistic infections were most frequent in patients with severe renal failure (p=0.018), and severe leukopenia (p<0.000). Fifty-one (20.7%) patients died: 33 with MPA, 15 with WG, and 3 with CSS. Mortality was significantly related to severe renal failure (p<0.000), nephrotic syndrome (p=0.001), hemoptisis (p=0.044), cardiac involvement (p=0.003), CVA (p=0, 042), sepsis (p=0.038) opportunistic infections (p=0.007), and neoplasm (p=0.023). Conclusions: The clinical characteristics seen here are similar to those in previous series. The presence of severe renal, pulmonary or cardiac involvement was significantly associated with a poor clinical outcome. MPA had a poorer prognosis that WG or CSS. References: Lane SE, Watts RA, Shepstone L, et al. Primary systemic vasculitis: clinical features and mortality. Q J Med 2005; 98:97-111 Disclosure of Interest: None Declared